RFID@B2B a Powerful Enabler of Business Transformation - Turcu, Cr.; Prodan, R.; Cerlincă, M.; Turcu, C.; Cerlincă, T. (Elektronika ir Elektrotechnika, 2009)
An RFID_B2B system that brings together the RFID and B2B advantages and which could be a powerful enabler of business transformation in the context of the globalization process is presented. The presented system helps small, medium and enterprise organizations to improve productivity and provide better service to their customers by providing a flexible solution for all of a company’s B2B needs. Ill. 1, bibl. 21 (in English; summaries in English, Russian and Lithuanian).